PROBLEM-BASED LEARNING METHODS IN DEVELOPING CRITICAL THINKING - Bog’ibekova Nurxonimjon Muzaffar qizi (Prospects for innovative technologies in science and education, 2025)
This research examines the pedagogical effectiveness of problem-based learning (PBL) in developing critical thinking skills. The study highlights the role of PBL in enhancing students’ critical thinking, independent learning, creative problem-solving, and collaborative skills. Furthermore, the impact of problem-based learning on metacognitive, social, and ethical development, its integration with modern educational technologies, and its effectiveness as confirmed by international studies are analyzed.